The Effectiveness of Spiritual Intervention in Overcoming Anxiety and Depression Problems in Gynecological Cancer Patients - Lina Anisa Nasution; Yati Afiyanti; Wiwit Kurniawati (Jurnal Keperawatan Indonesia, 2021)
Anxiety and depression are psychological distress that often occurs in gynecological cancer patients. However, there are few studies related to interventions to overcome these problems. The purpose of this study was to determine the effect of a spiritual intervention on anxiety and depression in such cancer patients. The research design was quasi-experimental, employing pretest and posttest on the intervention and the control groups. The total number of respondents was 108 patients, consisting of 54 in each group. The instrument used in the study was the Hospital Anxiety and Depression Scale (HADS). The spiritual intervention consisted of four sessions, namely an introduction and relaxation session, a control session, an identity session, and a relationship and prayer therapy session, held over two weeks. The data analysis showed a change in the mean score of anxiety and depression in the intervention group after the spiritual intervention (p = 0.001). Also, there were differences in the mean scores of anxiety and depression between the intervention and control groups (p = 0.001). The result implies that spiritual intervention can be applied as part of holistic nursing care for cancer patients, especially gynecological ones. Abstrak Efektifitas Intervensi Spiritual dalam Mengatasi Masalah Kecemasan dan Depresi pada Pasien Kanker Ginekologi. Kecemasan dan depresi merupakan gangguan psikologis yang sering terjadi pada pasien kanker ginekologi. Namun, penelitian terkait intervensi dalam mengatasi masalah tersebut belum banyak dilakukan. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh intervensi spiritual terhadap kecemasan dan depresi pada pasien kanker ginekologi. Desain penelitian ini adalah quasi eksperimen menggunakan kelompok intervensi dan kontrol dengan pre-test dan post-test. Jumlah responden sebanyak 108 pasien yang terdiri dari 54 orang di setiap kelompok. Instrumen yang digunakan dalam penelitian ini adalah Hospital Anxiety and Depression Scale (HADS). Intervensi spiritual terdiri dari empat sesi: sesi pengenalan dan relaksasi, sesi kontrol, sesi identitas, dan sesi terapi hubungan dan doa, yang diberikan selama dua minggu. Analisis data menunjukkan adanya perubahan rerata skor kecemasan dan depresi pada kelompok intervensi setelah diberikan intervensi spiritual (p = 0,001). Selain itu, terdapat perbedaan rerata skor kecemasan dan depresi antara kelompok intervensi dan kontrol (p = 0,001). Penelitian ini mengimplikasikan bahwa intervensi spiritual dapat diterapkan sebagai bagian dari asuhan keperawatan holistik pada pasien kanker, terutama yang ginekologi. Kata Kunci: depresi, intervensi spiritual, kanker, kecemasan